LC3 cementitious binder incorporating microencapsulated phase change materials for self-defrosting traffic surfaces - Kabay, Nihat; Miyan, Nausad; Omur, Tarik; Nehdi, Moncef L. (ELSEVIER SCI LTD, 2024)
Exposed surfaces of bridge decks, viaducts and pavements incur ice formation and accumulation of snow in cold seasons, which threatens traffic safety. Mitigating this problem using traditional methods such as deicing salts have caused ecosystem damage and inflicted substantial reinforcement corrosion and surface scaling to bridge decks and pavements, thus compromising their service life and causing colossal economic loss. This paper presents an alternative solution to overcome this problem through the development of a sustainable LC3 cementitious material incorporating micro-encapsulated phase change material (MEPCM) with low phase transition temperature to delay the surface temperature drop and mitigate snow accumulation and ice formation. MEPCM was incorporated in the cementitious matrix at 0 %, 10 % and 20 % by binder mass. Paste and mortar mixtures were prepared to investigate the microstructural, mechanical, physical, and thermal properties. Test results showed that incorporating MEPCM in the LC3 matrix achieved adequate compressive strength. Thermal simulations and visual observations conducted on mortar samples in the laboratory and outdoor exposure showed that MEPCM can effectively regulate the surface temperature of the LC3 matrix and mitigate temperature drops as well as snow accumulation. Analysis of temperature data in the 2023-2024 winter season of Hamilton, Ontario, Canada indicated that the MEPCM incorporated in mortar samples could effectively regulate 40 % of the total days considered and mitigate surface ice formation and snow accumulation, which provides both economic and environmental benefits.
Keywords: Phase change material; Limestone calcined clay cement; Snow; Deicing; THERMAL-ENERGY STORAGE; CONCRETE PAVEMENT; CARBON-FIBER; PCM; COMPOSITES; Construction & Building Technology; Engineering; Materials Science